2015
DOI: 10.1002/pon.3981
|View full text |Cite
|
Sign up to set email alerts
|

Patients are dissatisfied with information provision: perceived information provision and quality of life in prostate cancer patients

Abstract: A third of all prostate cancer survivors reported to be dissatisfied with the information received and scored worse on HRQoL and illness perception. A prospective randomized study is needed to study the effect of an intervention that improves information provision on HRQoL and illness perception outcomes. Copyright © 2015 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 31 publications
2
42
1
2
Order By: Relevance
“…In previous studies, a majority of patients with various cancer types have reported not being satisfied with the amount of information they received (eg, breast [36%], urological [34%], endometrial cancer [41%], melanoma [61%], and lymphoma and multiple myeloma [33%]), similar to our study (45%) . Patients not satisfied with the information provision reported lower scores on all subscales of provided information compared with satisfied patients.…”
Section: Discussionsupporting
confidence: 83%
“…In previous studies, a majority of patients with various cancer types have reported not being satisfied with the amount of information they received (eg, breast [36%], urological [34%], endometrial cancer [41%], melanoma [61%], and lymphoma and multiple myeloma [33%]), similar to our study (45%) . Patients not satisfied with the information provision reported lower scores on all subscales of provided information compared with satisfied patients.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, an indifferent attitude towards OACA, including rather low concerns and low necessity beliefs (vs. an accepting attitude) was associated with information dissatisfaction. In other studies, it was also observed that the beliefs of cancer patients influence information satisfaction [18,31,32]. Information on Oral Anticancer Agent Use C. C. L. M. Boons et al…”
mentioning
confidence: 91%
“…Interestingly, very satisfied patients had received more information than those less satisfied, but reasons for this discrepancy were not determined. A cross‐sectional study involving 697 men with PC by Lamers et al () reported on data collected in the Netherlands in 2011, with the study focussing on cancer survivors, rather than patients undergoing active treatment. 34% of participants reported dissatisfaction with information provision, but the nature of information was found to be helpful by 72%.…”
Section: Resultsmentioning
confidence: 99%
“…Studies by Majumder et al () and Lamers et al () are similar in that they used the same data collection instruments (EORTC QLQ‐C30 and EORTC‐INFO25 questionnaires designed to elicit information on quality of life and information preferences) and surveyed a similar number of men with PC ( n = 656 vs. n = 688). Majumder et al () focussed on men with PC treated with radiotherapy and Lamers et al () on men with PC who had received any treatment type. There was broad agreement in the study findings with the mean scores for overall satisfaction being 69% and 66%, respectively, which also compares well with the 74% reported by Adler et al ().…”
Section: Resultsmentioning
confidence: 99%